First-order modular logic programs and their conservative extensions. Issue 5 (14th October 2016) - HARRISON, AMELIA; LIERLER, YULIYA
Abstract: Modular logic programs provide a way of viewing logic programs as consisting of many independent, meaningful modules. This paper introduces first-order modular logic programs, which can capture the meaning of many answer set programs. We also introduce conservative extensions of such programs. This concept helps to identify strong relationships between modular programs as well as between traditional programs. We show how the notion of a conservative extension can be used to justify the common projection rewriting.